(untitled) (The Science Post, 2025)
This paper discusses the pedagogical and institutional implications of integrating professional filmmakers into higher learning education technology programs in Kuwait. This study tests the influence of filmmaker-based teaching on the creative growth of students, technical skills, and general educational experience in an environment where the use of video production and digital storytelling is becoming more relevant as an effective learning method. The combination of quantitative and qualitative data was used: 134 students participated in pre- and post-course surveys, qualitative information was supplemented by the focus groups with teaching staff, and four guest filmmakers were interviewed. The findings showed a great deal of improvement in video production skills and critical thinking, as well as student engagement, the relevance and authenticity of the curriculum. The cooperation of the institution and professionals in the field of creative industries was also discovered to lead to the improvement of interdisciplinary teaching activities and innovation in the curriculum. However, other problems were noticed: pedagogical dissonance, weak training of filmmakers who lacked any experience in teaching, and rigidity of the institutions. It is on this basis that the study concludes the importance of the role of filmmaker’s involvement in acting as a transformative educational strategy once there is adequate support and successful collaborative structures in place. The results have realistic implications for the practices of educators, curriculum developers, and policymakers within institutions that aim to modernize media education and decrease the existing distance between institutional theories and practices.